(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
As we approach a world of globalization and rapid advancement of technology, it has become essential for people to speak multiple languages not only to foster their career opportunities, promote personal growth, enable travel abroad, but also to build meaningful relationships. Although reading and writing skills are important in language acquisition, speaking remains the most challenging and anxiety-inducing aspect of a foreign language, highlighting the need for teachers to implement interactive methods, actively guide and motivate students. This difficulty is largely due to common traditional way of teaching students through rote memorization, grammar, test-based classes, and the feeling of reluctance to learn a language rather than authentic communication, thereby reducing students’ motivation and passion. However teachers can create an environment, where students feel nothing but passion, energy, and eagerness to acquire a new language by facilitating modern and student-centered classes. It is usually lack of confidence and practical skills that many students struggle from. Speaking ability goes beyond the mere use of words to express thoughts; it also requires emotional engagement, creativity, and spontaneity. The greatest problem many people face today is finding effective, innovative, and accessible methods to improve speaking ability in a foreign language. This article examines the indispensable role of teachers in helping learners enhance their speaking proficiency through social learning approaches and evidence-based practical techniques such as debates, drama, and storytelling.